Canning of Edible Oyster Meat - BALACHANDRAN, K K; VIJAYAN, P K; PRABHU, P V (Fishery Technology, 2017)
Results of experiments carried out on canning edible oyster ( Crassostrea madrasensis) meat from farmed as well as wild specimens are discussed. The canning yield of meat was 15% higher from farmed oysters compared to wild specimens. The meat from wild oysters was highly slimy and therefore required an additional pre-treatment of washing in brine containing acetic acid to prevent formation of lumps of meat in the can causing problems for proper heat penetration while processing.